2018
DOI: 10.1186/s13104-018-3787-6
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric variables as predictors of aspects of quality of life in persons with central obesity

Abstract: ObjectiveCentral obesity has been shown to negatively influence the quality of life in centrally obese persons of both sexes. In a population of 740 centrally obese Asian-Indian adults, the present study was conducted to determine whether body mass index (BMI), waist circumference, hip circumference (HC), waist-hip ratio (WHR) and sagittal abdominal diameter (SAD) could predict different domains of quality of life. The differences based on gender and age were also determined. Linear regression analyses were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…It is interesting to note that when eating habits and physical condition were combined, overweight and obese middle-aged and older adults with low AMedDiet and low CRF showed higher SBP, MBP, DP, fat mass, BMI, PI, and WHR than the group with a low AMedDiet and high CRF and/or high AMedDiet and high CRF. This confirms that both aspects are associated with BP variables [ 2 , 3 ], body composition, and proportionality variables related to obesity [ 58 , 61 , 74 , 75 ], although CRF seems to have somewhat more importance than diet habits [ 58 , 61 ]. A possible explanation for this might be that overweight and obese people, especially during the aging process, have some hormonal and hemodynamic changes which are associated with hypertension [ 78 ] and changes in body composition and physiology of fat [ 79 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is interesting to note that when eating habits and physical condition were combined, overweight and obese middle-aged and older adults with low AMedDiet and low CRF showed higher SBP, MBP, DP, fat mass, BMI, PI, and WHR than the group with a low AMedDiet and high CRF and/or high AMedDiet and high CRF. This confirms that both aspects are associated with BP variables [ 2 , 3 ], body composition, and proportionality variables related to obesity [ 58 , 61 , 74 , 75 ], although CRF seems to have somewhat more importance than diet habits [ 58 , 61 ]. A possible explanation for this might be that overweight and obese people, especially during the aging process, have some hormonal and hemodynamic changes which are associated with hypertension [ 78 ] and changes in body composition and physiology of fat [ 79 ].…”
Section: Discussionsupporting
confidence: 66%
“…Although body composition is influenced by physical practice and diet habits [58], increased total fat, particularly abdominal fat, are key features of obese and aging [73]. The results of this study determined that overweight and obese middle-aged and older adults showed healthy values in trunk and total fat and in other proportionality parameters related with obesity [74,75] such as BMI, PI, biiliocristal/biacromial ratio, and WHR when having a high CRF. Previous studies have found that aerobic exercise training or combined aerobic and resistance training can change anthropometric parameters and body composition, related to an improvement in BP parameters [58,61].…”
Section: Discussionmentioning
confidence: 71%
“…Todos los antecedentes encontrados, evidencian a una gran cantidad de evaluados con sobrepeso, obesidad y riesgo metabólico, situándolos en una situación preocupante debido a la relación que tienen el IMC y el ICC con un aumento del riesgo de mortalidad (Telles, Kala, Sharma & Balkrishna, 2018;WHO, 2011), pero por otro lado son alentadores debido a que demuestran que la práctica del deporte podría ser un medio que ayude a mejorar los valores de RCR y tejido muscular, lo cual contribuiría a reducir el riesgo que generan altos valores de IMC e ICC (Lin et al, 2015). Además de lo anterior, el que sean sujetos físicamente activos, los ayuda a tener menor riesgo de mortalidad por eventos cardiovasculares, a pesar de obtener altos valores de IMC o tejido adiposo, debido al factor protector que provoca la actividad física (McAuley et al, 2012) Las principales fortalezas de esta investigación están en: 1) generar información sobre características morfológicas e índices evaluados, la cuales pueden ser de utilidad para entrenadores o investigadores que deseen realizar comparaciones, 2) entregar información sobre una capacidad poco evaluada en estos deportistas RCR.…”
Section: Discussionunclassified
“…Algo similar ocurre con el diámetro antero-posterior del abdomen, considerado otro indicador de obesidad central al estar relacionado con la masa grasa visceral, la que conlleva mayor riesgo cardiovascular (Da Silva-Ferreira et al 2012). Por un lado, existen estudios que posicionan su punto anatómico de referencia en el diámetro máximo del abdomen en el plano sagital (Da Silva-Ferreira et al 2012), mientras que, por otro lado, otros lo sitúan a nivel del ombligo (Da Silva-Ferreira et al 2012), justo en el relieve de su parte más inferior (Esparza-Ros et al 2019), e incluso otros en el punto medio entre las crestas ilíacas, coincidiendo con las vértebras lumbares L4 y L5 (Da Silva-Ferreira et al 2012, Duarte Pimentel et al 2010Telles et al 2018). Este último punto es el más empleado en la práctica clínica ya que es el que mayor correlación con el volumen de masa grasa visceral (Da Silva-Ferreira et al 2012).…”
Section: Medida Antropométrica -Pliegues Enlaceunclassified